2023
DOI: 10.1113/jp284449
|View full text |Cite
|
Sign up to set email alerts
|

The jugular venous‐to‐arterial PCO2${P_{{\mathrm{C}}{{\mathrm{O}}_{\mathrm{2}}}}}$ difference during rebreathing and end‐tidal forcing: Relationship with cerebral perfusion

Jay M. J. R. Carr,
Trevor A. Day,
Philip N. Ainslie
et al.

Abstract: We examined two assumptions of the modified rebreathing technique for the assessment of the ventilatory central chemoreflex (CCR) and cerebrovascular CO2 reactivity (CVR), hypothesizing: (1) that rebreathing abolishes the gradient between the partial pressures of arterial and brain tissue CO2 [measured via the surrogate jugular venous and arterial difference (Pjv‐aCO2)] and (2) rebreathing eliminates the capacity of CVR to influence the Pjv‐aCO2 difference, and thus affect CCR sensitivity. We also evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Methodological considerations regarding variability between individuals and the influence of hyperoxia on cerebral vasoconstriction were discussed (Carr et al, 2023). For example, Mattos et al (2019) found that a 10 min exposure of isocapnic hyperoxia (100% F IO 2 ) decreased CBF by ∼63 mL/min compared to normoxia (21% F IO 2 ).…”
Section: Cerebral Circulation Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodological considerations regarding variability between individuals and the influence of hyperoxia on cerebral vasoconstriction were discussed (Carr et al, 2023). For example, Mattos et al (2019) found that a 10 min exposure of isocapnic hyperoxia (100% F IO 2 ) decreased CBF by ∼63 mL/min compared to normoxia (21% F IO 2 ).…”
Section: Cerebral Circulation Considerationsmentioning
confidence: 99%
“…Recently, in the Journal of Physiology, Carr et al (2023) carefully quantified the arterial-to-jugular venous P CO 2 difference (P jv−a CO 2 ) and its association with middle cerebral artery blood velocity (MCAv, a proxy measurement for CBF) during hyperoxic hypercapnic modified rebreathing and during two protocols of a hypercapnic end-tidal forcing (ETF) technique. With the ETF method, participants were exposed to different progressive isocapnic levels until a physiological steady state occurs (i.e.…”
mentioning
confidence: 99%
“…In this issue of The Journal of Physiology, Carr et al (2023) have shown via careful experimentation in healthy humans that equilibrium of arterial with jugular venous bulb CO 2 (assumed to represent the P CO 2 in medullary chemosensitive sites) is not achieved at any time during hyperoxic rebreathing. Rather, the arterial-jugular venous P CO 2 difference was quickly reduced to about half its air-breathing control value at the onset of rebreathing but then, on average, remained at this substantial gradient despite a rising CBF as P aCO 2 rose with continued rebreathing.…”
mentioning
confidence: 99%
“…Accordingly, the present findings showed that although the arterial-to-jugular venous bulb P CO 2 difference was substantial and did show considerable within-and between-subject variability as P aCO 2 rose during rebreathing, importantly, on average the jugular venous P CO 2 rose in parallel with P aCO 2 . Thus, Carr et al (2023) felt justified in proposing that the modified rebreathing method was '…ideal for assessing central CO 2 chemosensitivity independent of the confounding influence of an increase in CBF'! We agree that the present findings support this recommendation.…”
mentioning
confidence: 99%
See 1 more Smart Citation